Instructional analogies and conceptual change: the role of prior knowledge in understanding counter-intuitive scientific information through the use of instructional analogies - Skopeliti, Irini; Vosniadou, Stella (Psychology: the Journal of the Hellenic Psychological Society, 2022)
Previous research on instructional analogies used in scientific texts explaining counter-intuitive scientific information, meaning that they are in complete contradiction to their everyday experiences, has shown that they can promote the learning process. High correlation was found between the readers’ prior knowledge and the positive effects of the analogy since the participants with more sophisticated prior knowledge showed better understanding of the analogies and learning improvement in the posttest. Unexpectedly, however, there were participants with naive prior knowledge who showed complete understanding of the analogies used and also participants who, although they understood the analogy, did not show learning improvement in the posttest. These findings led to an interview study, which investigated in greater detail the relations between prior knowledge, analogy understanding and acceptance of the scientific explanation presented in texts. The participants of the study were 3rd and 5th grade elementary school students. We used an open-ended questionnaire, which investigated students’ knowledge about the Earth and the day/night cycle and two explanatory texts. One text explained the day/night cycle using an instructional analogy, while the other gave the scientific explanation of day/night cycle without the use of the analogy. We hypothesized that the understanding the scientific explanation and the analogy requires an improved, sophisticated prior knowledge of the Earth as a spherical astronomical object that is guided by sophisticated ontological and epistemological beliefs. The results of the study confirmed our hypothesis and showed that even when the scientific explanation is understood -a process facilitated by the use of instructional analogies- it is significantly difficult for the students to accept the scientific explanations when these are counter-intuitive and in complete contradiction to their everyday experiences and their epistemological beliefs are not sophisticated but prevented by the belief that “things are as they appear to be”. Consequently, it appears that additional educational practices can be used to reinforce the positive outcomes of the instructional analogies.